(untitled) (National Administration Journal, 2020)
Telework could become an alternative that may enable the business sector and the worker to obtain a win-win relation to move on in view of the global situation of the enterprises. This article aims at identifying the factors that may enable the worker, from the perspective of the business sector, to carry out activities according to the expectations of the enterprise and reach the goals established as part of the job post. The information was gathered by means of in-depth interviews and surveys to enterprises that have implemented this modality with success and have reached the goals established as organizations.